Ginsenoside Rh4 Inhibits Colorectal Cancer Cell Proliferation by Inducing Ferroptosis via Autophagy Activation. (29th May 2022) - Wu, Yingchao; Pi, Dajin; Chen, Yiliu; Zuo, Qian; Zhou, Shuyao; Ouyang, Mingzi
Abstract : Colorectal cancer (CRC) is a severe threat to human health. Ginsenosides such as ginsenoside Rh4 have been widely studied in the antitumor field. Here, we investigated the antiproliferative activity and mechanism of Rh4 against CRC in vivo and in vitro. The CRC xenograft model showed that Rh4 inhibited xenograft tumor growth with few side effects (p < 0.05 ). As determined by MTT colorimetric assays, Western blotting, and immunohistochemical analysis, Rh4 effectively inhibited CRC cell proliferation through autophagy and ferroptosis (p < 0.05 ). Rh4 significantly upregulated autophagy and ferroptosis marker expression in CRC cells and xenograft tumor tissues in the present study (p < 0.05 ). Interestingly, the ferroptosis inhibitor ferrostatin-1 (Fer-1) reversed Rh4-induced ferroptosis (p < 0.05 ). Moreover, the autophagy inhibitor 3-methyladenine (3-MA) also reversed Rh4-induced ferroptosis (p < 0.05 ). These results indicate that Rh4-induced ferroptosis is regulated via the autophagy pathway. In addition, Rh4 increased reactive oxygen species (ROS) accumulation, leading to the activation of the ROS/p53 signaling pathway (p < 0.05 ). Transcriptome sequencing also confirmed this (p < 0.05 ). Moreover, the ROS scavenger N-acetyl-cysteine (NAC) reversed the inhibitory effect of Rh4 on CRC cells (p < 0.05 ). Therefore, this study proves that Rh4 inhibits cancer cell proliferation by activating the ROS/p53 signaling pathway and activating autophagy to induce ferroptosis, which provides necessary scientific evidence of the great anticancer potential of Rh4.